If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1(x + 3) = (2x + 5) Reorder the terms: 4x + -1(3 + x) = (2x + 5) 4x + (3 * -1 + x * -1) = (2x + 5) 4x + (-3 + -1x) = (2x + 5) Reorder the terms: -3 + 4x + -1x = (2x + 5) Combine like terms: 4x + -1x = 3x -3 + 3x = (2x + 5) Reorder the terms: -3 + 3x = (5 + 2x) Remove parenthesis around (5 + 2x) -3 + 3x = 5 + 2x Solving -3 + 3x = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 3x + -2x = 5 + 2x + -2x Combine like terms: 3x + -2x = 1x -3 + 1x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 1x = 5 + 0 -3 + 1x = 5 Add '3' to each side of the equation. -3 + 3 + 1x = 5 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 5 + 3 1x = 5 + 3 Combine like terms: 5 + 3 = 8 1x = 8 Divide each side by '1'. x = 8 Simplifying x = 8
| (2x-3)*(x+5)+7=(x-4)*(2x-1)+2 | | x/2+x/3+200=x | | 4x^2=13x-3 | | -1*25= | | 3x+2y=4z | | (3p^2-3p-5)-(2p^2-2p-5)=0 | | 3g^2+20g+32=0 | | 4(2Q+5)=3(Q+10) | | 19+(-18)-(-20)-7+(-9)= | | 7r^2-9r-10=0 | | t^3-10t^2+29t=0 | | (5x^2-2x-1)-(x^2-3x-5)=0 | | 48h^2+-86h+35=0 | | t-2(3-2t)=2t+9 | | 2(x+4)=x | | 3*(250-x)=250+x | | -6x+8=58-x | | 9x^2+9x+9=0 | | 24m^2+18m-15=0 | | (6-2)(5-8)= | | 6x-6=7(x-9) | | 4x+2=9-(9x-9) | | x^2-9x=1 | | 3x+4(2x-1)= | | 0.8x-0.6(4-x)=5.3 | | 6a-3(a+2)= | | 1x-10+x-5x+1=14+3x-8-1 | | 4xy-5y+2=0 | | -2x=3(x-5)+6 | | 3x-10=-4x+22 | | 3p(p-1)=18 | | 7x=50-1 |